2021
DOI: 10.3390/nursrep11020031
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Civility, Respect, and Engagement in the Workplace (CREW) Program on Social Climate and Work Engagement in a Psychiatric Ward in Japan: A Pilot Study

Abstract: Background: Good social climate and high work engagement are important factors affecting outcomes in healthcare settings. This study observed the effects of a program called Civility, Respect, and Engagement in the Workplace (CREW) on social climate and staff work engagement in a psychiatric ward of a Japanese hospital. Methods: The program comprised 18 sessions installed over six months, with each session lasting 30-min. Participation in the program was recommended to all staff members at the ward, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Any disagreements on eligibility were resolved through discussions with the last author (HF). For example, we discussed whether a paper19 could be accepted as an eligible article because it included nurses, clinicians and others in a psychiatric ward as participants in a WE intervention. However, more than half of the participants were found to be non-nurses at certain points between the four time points (baseline, midpoint, post and 1-month post); therefore, we opted to exclude this article based on the exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Any disagreements on eligibility were resolved through discussions with the last author (HF). For example, we discussed whether a paper19 could be accepted as an eligible article because it included nurses, clinicians and others in a psychiatric ward as participants in a WE intervention. However, more than half of the participants were found to be non-nurses at certain points between the four time points (baseline, midpoint, post and 1-month post); therefore, we opted to exclude this article based on the exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0262-1711.htm (Campbell et al, 2021;der Kinderen et al, 2020), social climate (Sawada et al, 2021); team humility (Rego and Simpson, 2018); OCB (Myers et al, 2016); work engagement (Sawada et al, 2021); and organizational performance (Oppel et al, 2019). Civility climate is also confirmed to reduce employee deviance and burnout (Clark and Walsh, 2016;Laschinger and Read, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…, 2021; der Kinderen et al. , 2020), social climate (Sawada et al. , 2021); team humility (Rego and Simpson, 2018); OCB (Myers et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for Achmadi et al ( 2022) study, in the context of climate, several researchers have proven the role of leader humility. For example, leader humility relates to social climate (Sawada et al, 2021). Furthermore, although not specific to leader humility, Bunce (2021) found that leadership is essential in developing a civility climate.…”
Section: Leader Humility and Civilitymentioning
confidence: 99%